Formulation and Evaluation of Polyherbal Gel containing Azadirachta indica (Neem), Ocimum sanctum (Tulsi), and Trigonella foenum-graecum (Fenugreek) for Antifungal Action - Bhati, Jyoti; Mittal, Anuj (Journal of Neonatal Surgery, 2025)
The escalating prevalence of dermatophytic infections and the emergence of antifungal resistance have necessitated the development of novel, plant-based therapeutics with improved biocompatibility, safety, and efficacy. This study reports the formulation and comprehensive evaluation of a polyherbal topical gel incorporating extracts from Azadirachta indica (Neem), Ocimum sanctum (Tulsi), and Trigonella foenum-graecum (Fenugreek), aimed at enhancing antifungal action through synergistic phytochemical interactions. Using carbopol 940 as the gelling agent, a series of formulations (PHG1 to PHG8) with varying concentrations of the polyherbal extracts were prepared and assessed for their physicochemical attributes including pH, viscosity, homogeneity, spreadability, and extrudability. The antifungal efficacy was evaluated using the agar well diffusion method against Candida albicans and Aspergillus niger, benchmarked against standard antifungal agents. Formulation PHG4, containing 4% polyherbal extract, demonstrated optimal viscosity (4520 ± 15 cP), suitable spreadability (6.2 ± 0.1 cm), and a pH of 6.1 ± 0.2, indicating compatibility with the physiological skin environment. Notably, PHG4 exhibited a significant antifungal zone of inhibition (23.6 ± 0.3 mm) against C. albicans, closely approximating the performance of the standard drug fluconazole (25.1 ± 0.2 mm). Statistical analysis revealed significant differences (p < 0.05) between lower-concentration batches and PHG4, highlighting its potential as an effective alternative to synthetic formulations. The results underscore the efficacy of synergistically combined herbal extracts in a semisolid vehicle, offering a promising approach to combat fungal infections while minimizing the risk of resistance and adverse reactions.